Role of l-glutamine in the in-vitro growth of HCT-8 and HT-29 cell lines = Peranan l-glutamin dalam pertumbuhan sel HCT-8 dan HT-29 in-vitro - Mat Yusof, Afzan; Jainul, Mohammed Abdullah (Malaysian Analytical Science Society, 2019)
L-glutamine is one of the essential supplements of in-vitro growth medium for cancer cells. The amino acid L-glutamine is well known as the vital source of nutrition in cancer cell growth for its ability to provide carbon and nitrogen. A common phenomenon of cancer cell is the rapid production of lactic acid through aerobic glycolysis. Apart from nutritional value, the released ammonia from L-glutamine may neutralize the acidic environment to ensure continuous cell growth. The current study is to observe the effect of L-glutamine concentration in culture media for cancer cell lines. Detection of L-glutamine consumption by the cells was carried out after 8 hours of incubation period. Numerous culture media were prepared adding L-glutamine concentration of 0 mM, 5 mM and 10 mM with different pH range. The cell density was calculated after 8 hours of incubation using trypan blue staining method. UV-Vis spectrophotometer was used to detect the concentration of L-glutamine consumption. The result shows that the cell density did not increase significantly in the media without L-glutamine supplement whereas, a rapid increase was observed in L-glutamine supplemented growth media in HCT-8 and HT-29 cell lines. The L-glutamine consumption was found higher in the media with low pH, but a relatively low L-glutamine consumption was observed in media with higher pH condition. The result confirms the necessity of L-glutamine in cancer cell growth. In addition, higher L-glutamine uptake in acidic condition supports the role of L-glutamine in acid resistance activity in cancer cell growth.